The herpes simplex virus type 1 major capsid protein (VP5-UL19) promoter contains two cis-acting elements influencing late expression. - Huang, C J (1994)
The herpes simplex virus type 1 (HSV-1) major capsid protein VP5 gene (UL19) is expressed with beta gamma (gamma 1 [leaky late]) kinetics. We have previously described the construction of recombinant HSV-1 in which the VP5 promoter was engineered to control the expression of the bacterial beta-galactosidase gene as a reporter (C.-J. Huang, S. A. Goodart, M. K. Rice, J. F. Guzowski, and E. K. Wagner, J. Virol. 67:5109-5116, 1993). Here we describe further mutational analysis in recombinant viruses. We have precisely defined the boundaries of the VP5 promoter and identified two regions important for both the level and the kinetics of expression. The 5' boundary was located at -48 relative to the initiation site of transcription by analyzing a series of nested deletions in the upstream sequence, and although a number of cis-acting sites influencing transient expression have been identified upstream of this point, these sites have no role in promoter activity during productive infection. Deletion of an Sp1-binding site located between -48 and the TATA box at -30 greatly reduced VP5 promoter activity late but not early after infection. A cis-acting element whose sequence resembles the human immunodeficiency virus type 1 initiator was located between -2 and +10 in the VP5 sequence by characterizing a series of deletions and site-directed block mutations downstream the TATA box. This element defines the 3' limit of the VP5 promoter, and like the upstream element, disruption of this element also inhibited promoter activity late in the productive cycle.